Avaliação do perfil de expressão de genes envolvidos na tumorigênese, proliferação e malignidade de células leucêmicas K562, sem e sob tratamento, com o composto antitumoral A398 - Arruda, Isabela Tatiana Sales de (2019)
A human chronic myeloid leukemia, a hematologic malignancy, is characterized by a disorder of stem cells and deregulation of predominantly myeloid cell growth in the bone marrow generating accumulation of cells without peripheral blood. The product A398, a semisynthetic product, analogue of podophyllotoxin, has been studied by our group of researchers. In this context, our study evaluated the relationship between the anticancer activity of the exercise and the expression of cell death, events and interventions inherent to the onset of leukemia, aiming at proposing new therapeutic drugs for the diagnosis, malignancies. Initially, a toxicity of compound A398 against K562 cells was investigated by the MTT method. We found that compound A398 at IC50 = 8 μM for 24 h was cytotoxic to K562 cells and was not cytotoxic to PBMC, control group. The analysis of the genes involved in the tumor characteristics of K562, without treatment with compound A398, was performed by the macroarray technique with the Taqman® acquisition system. We first plot the expression profile of genes such as STAT3, ISYNA1, TGFB1, HIF1A, VEGFA, CCR7, MMP9, ALOX5, CASP1, IL1B, IL6, IL8, NFKB1, TNFRSF11A, NFKB2, RELA, TNFA, cJUN, BCL2, BCL2L1, BAX, BAK1, BIN1, BID, PMAIP1, CYCS, CASP9, CASP8, CASP3, CASP7, CASP7, FAS, FADD involved with tumorigenic processes related to inflammation and cell death in untreated K562 cells compared to healthy PBMC cells. We used the 18S, GAPDH, B2M and ACTB endogenous genes in our expression assays. Our data demonstrated that K652 cells exhibited pattern of gene expression that favored the progression of leukemia when compared to PBMC cells. We observed that genes involved in the regulation of proliferation, invasion, and metastasis of K562 cells had altered expression profile when treated with compound A398 favoring the onset and progression of chronic myeloid leukemia. The TNFRSF11A, STA3, CCR7, cJUN, TNFA and ALOX5 genes involved in the modulation of the inflammatory response were inhibited in the K562 cells treated by compound A398. The anti-apoptotic genes BCL2 and FADD showed their inhibited expression in K562 cells treated by compound A398. The pro-apoptotic genes PMAIP1, CYCS and BAX, showed increased expression in K562 cells treated by compound A398. We performed the flow cytometry assay using the externalization technique of phosphatidylserine on K562 cells under treatment with compound A398 at 8 μM for 24 h and we observed that the compound induces cell death. We suggest that the mechanism of cell death would be by necroptosis. Our results demonstrated that the treatment of K562 cells with anti-tumor compound A398 modulates the expression of genes involved in tumorigenesis, proliferation and malignancy of leukemic cells and appears to be inducing necroptosis cell death, these findings corroborate with the anticancer profile of compound A398, as well as, creates perspectives for a new route of studies for compound A398 as an antileukemic agent.